UPAYA PENGAKARAN Echinacea purpurea L DENGAN AUKSIN SECARA KULTUR JARINGAN - Heru Sudrajat (Universitas Trunojoyo Madura, 2013)
Recently, to meet the needs of botanicals medicinal plants the cultivation directed, require good quality and uniform seeds on form and time. Tissue culture research to from root of Echinacea purpurea L by the provision of IBA and NAA will be conducted.This recearched aimed to develop an and cultivate qualified Echinacea purpurea L as the raw material for drug foemulation. Tissue culture techniques has more advantage because it is not affected by the climate, relatively fast production, free contamination of microbial and do not require large tracts of land. The research was carried out considering the need to be developed and cultivated plant Echinacea purpurea L qualified as raw material for the drug tissue culture techniques has advantages because it is not affected by the climate with relatively fast production time, free of microbial contamination and do not require large tracts of land. Shoots multipication done on MS medium using growth regulators GA3with concentration of 3 mg / l. Research foor rof induction on Echinacea purpurea L shoot made by adding growth regulators of IBA and NAA with concentrations with 0, 2, 4 and 6 mg / l respectively. The 2 months incubation periods produced tehe best root induction on the additon of IBA 4 mg / l. It producted 16 roots with a length of 4 cm and relatively lagre in size.Keywords: Echinacea purpurea L., tissue culture, IBA, NAA, plant growth regulators